A new mucocutaneous activity index for Behçet's disease - (:unkn) unknown (Clinical and Experimental Rheumatology S.A.S., 2014)
Objective: Patient-reported outcomes are increasingly accepted to be major domains in chronic disorders. The aim of this study was to develop a patient-derived disease activity index in Beh-çet's disease (BD). Methods: One hundred and seventy-seven BD patients (M/F: 69/108) were included in the study. Data were collected by clinical examination and a questionnaire regarding a Mucocutaneous Index (MI) with genital ulcer activity (GI), erythema nodosum activity (EI) and the composite index (CI) for oral ulcers, as subscales of it. Self-reported treatment evaluation was carried out as criterion validity. Patients whose symptoms completely disappeared or decreased significantly, were categorised as "improved group", others were classified as "non-improved group". Results: Among the study group, 79.7% of the patients (n=141) were active, whereas 20.3% were inactive (n=36). Scores of CI, GI, EI and MI score were 0±0 in inactive ones, whereas scores were 5.65±2.36 for CI, 0.81±2.34 for GI, 0.91±2.35 for EI and 6.25±5.1 for MI in actives (p=0.000 for all). MI score was significantly higher in "non-improved group" (65.5%) compared to "improved group" (34.5%) (p < 0.0001). Conclusions: The mucocutaneous activity index may help decision-making process for treatment strategies in BD patients. © Clinical and Experimental Rrheumatology 2014.
Keywords: Activity; Behçet's disease; Index; Mucocutaneous; Symptoms; Treatment